Albatrosses respond adaptively to climate variability by changing variance in a foraging trait. (29th July 2021) - Patrick, Samantha C.; Martin, Julien G. A.; Ummenhofer, Caroline C.; Corbeau, Alexandre; Weimerskirch, Henri
Abstract: The ability of individuals and populations to adapt to a changing climate is a key determinant of population dynamics. While changes in mean behaviour are well studied, changes in trait variance have been largely ignored, despite being assumed to be crucial for adapting to a changing environment. As the ability to acquire resources is essential to both reproduction and survival, changes in behaviours that maximize resource acquisition should be under selection. Here, using foraging trip duration data collected over 7 years on black‐browed albatrosses ( Thalassarche melanophris ) on the Kerguelen Islands in the southern Indian Ocean, we examined the importance of changes in the mean and variance in foraging behaviour, and the associated effects on fitness, in response to the El Niño Southern Oscillation (ENSO). Using double hierarchical models, we found no evidence that individuals change their mean foraging trip duration in response to a changing environment, but found strong evidence of changes in variance. Younger birds showed greater variability in foraging trip duration in poor conditions as did birds with higher fitness. However, during brooding, birds showed greater variability in foraging behaviour under good conditions, suggesting that optimal conditions allow the alteration between chick provisioning and self‐maintenance trips. We found weak correlations between sea surface temperature and the ENSO, but stronger links with sea‐level pressure. We suggest that variability in behavioural traits affecting resource acquisition is under selection and offers a mechanism by which individuals can adapt to a changing climate. Studies which look only at effects on mean behaviour may underestimate the effects of climate change and fail to consider variance in traits as a key evolutionary force. Abstract : Within individual variability in black‐browed albatross foraging trip duration in relation to the Southern Oscillation Index.